Feasibility Study of the Organisation of Intercity Fast Ship Lines – the Case of Croatia’s Maritime Passenger Transport - Plazibat, Veljko; Krčum, Maja; Bacalja, Bruna; Peronja, Ivan (Transactions on Maritime Science, 2024)
This study explores the scientifically based possibilities and potential effects of connecting cities in the Republic of Croatia through the organisation of intercity fast ship lines in maritime passenger transport. Through a meticulous analysis a model of an abstract type of transport has been chosen in order to estimate the possible contribution of intercity lines in maritime passenger transport towards the development of the transport system of the Republic of Croatia, and also to determine the feasibility of introducing these lines with the aim of achieving balance among certain forms of transport. The results of this research indicate the economic, environmental, and energy justification of the organisation of intercity fast ship lines and their competitiveness in comparison with other forms of transport.